Self-Efficacy, Social Support, Educational Environment, and Mental Health among University Students in Digital Era - Rafiah, Kurnia Khafidhatur; Hasan, Zidny Ilma; Rejito, Cattleya (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of self-efficacy, social support, and educational environment on students' mental health within the framework of Social Cognitive Theory. The study used a cross-sectional quantitative survey design with convenience sampling technique on 107 undergraduate students at several universities in West Java. Data were collected through a 1–5 Likert scale questionnaire and analyzed using PLS-SEM. The results showed that the model had moderate explanatory power, with an R² value of 0.423 for mental health, meaning the three predictors together explained 42.3% of the variance in students' mental health. Specifically, social support had the largest positive effect on mental health (β = 0.372), followed by the educational environment (β = 0.214) and self-efficacy (β = 0.180). All three paths were statistically significant (p < 0.05), indicating that the higher the social support, perception of a supportive educational environment, and self-efficacy, the better the students' mental health. These findings confirm that interventions to improve student mental health need to prioritize strengthening social support, followed by improvements in the quality of the learning environment, and programs to increase self-efficacy. This study recommends that universities develop integrated programs that strengthen peer communities, enhance the role of lecturers as sources of support, and create an inclusive and mentally health-friendly learning environtment.